(untitled) (University of Thi-Qar Journal for Engineering Sciences, 2019)
A numerical study of three – dimensional, steady, laminar and incompressible natural convection of air (Pr=0.72) within a rectangular solar chimney is presented. Partial differential equations for conservation of mass, momentum and energy equations are solved by finite volume method with staggered grid arrangement. SIMPLE algorithm is applied to solve the set of discretization equations. The numerical results are compared with those of previous published work under the same conditions and gives a good agreement. The influence of changing in chimney dimension (thickness and height) and the inlet air temperature on the amount of induced flow rate is studied. From the presented results the optimal design for the chimney can be achieved